KADAR SURFACTANT PROTEIN-D SERUM PADA PASIEN PENYAKIT PARU OBSTRUKTIF KRONIS BERKEBAHAYAAN KAMBUHAN RENDAH DAN TINGGI - Dewi Nurhayati; Ida Parwati; Tiene Rostini; Arto Yuwono (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2016)
Chronic obstructive pulmonary disease (COPD) cause high morbidity and mortality worldwide. The exacerbations in chronicobstructive pulmonary disease accelerate the decline in lung function and health status, as well as in increasing the treatment cost andmortality risk. The spiro metric measurement has several limitations in assessing the severity as well as the exacerbation risk in COPDpatients. Currently, has been available serum surfactant protein-D, a marker of lung inflammation and lung tissue damage. This proteinis produced by the alveolar type II cells and the Clara cells that play role in maintaining the lung stability and pulmonary immunesystem. The increased level of serum SPD indicates that there is lung epitihelial leakage in line with COPD severity increment and reflectedin COPD exacerbation level of risk according to combined COPD assessment GOLD criteria of the year 2011. The aim of this study wasto know the differences of SP-D serum levels between low and high risk of exacerbation in COPD patients by determination them. Thisstudy was conducted from March to July 2014. The subjects of this study were COPD patients diagnosed by spiro metric measurement.The research was conducted in comparative analytic way with a cross sectional study design. The statistical analysis was performedusing Mann-Whitney non-parametric test. The subjects were 62 COPD patients. The SP-D serum level at low risk of exacerbation groupdiffer significantly compared to the high risk exacerbation group, 1.8–68.4 ng/mL and 3.36–116.4 ng/mL respectively (P=0.018).Based on this study it can be concluded that the SP-D serum levels were higher in COPD patients with high risk exacerbation than thelower risk one. The SP-D serum levels may be considered as a specific marker of lung tissue injury to assess the risk of the exacerbationin COPD patients.